Towards global competition: catalysts and constraints - Horst Siebert; Henning Klodt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The ongoing process of globalization, which is boosted by technological and political catalysts as well, increasingly raises public concerns. It is feared that international integration will be accompanied by national disintegration, since the income distribution in rich countries will become less uniform. Moreover, policy-makers become aware of the fact that global competition also encompasses their realm, because it constrains the scope for independent national policies. However, they should refrain from restricting global competition by protectionistic measures, because substantial gains from globalization for the world economy in general and terms-of-trade improvements for industrial countries in particular are at stake.
Keywords: F02; 330; Globalisierung; Internationaler Wettbewerb; Standortwettbewerb; Institutioneller Wettbewerb; Internationale Wirtschaftsbeziehungen; Welt